1993
DOI: 10.1021/bi00087a029
|View full text |Cite
|
Sign up to set email alerts
|

Expression and identification of p90 as the murine mitochondrial glycerol-3-phosphate acyltransferase

Abstract: Glycerol-3-phosphate acyltransferase (GPAT) catalyzes the initial and committed step in glycerolipid biosynthesis. Mitochondrial GPAT, unlike the microsomal isozyme, prefers saturated fatty acids as a substrate. We have recently reported cloning of a cDNA to an unidentified 6.8-kb mRNA by a differential hybridization. The mRNA contains an open reading frame of 827 amino acids (p90) with 30% sequence homology in a 300 amino acid stretch to Escherichia coli GPAT. The 6.8-kb mRNA was induced dramatically when fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 28 publications
(34 reference statements)
5
64
0
Order By: Relevance
“…The mitochondria were not contaminated with endoplasmic reticulum (Table I), and no immunoreactive protein was detected in the microsome fraction (Fig. 3A), consistent with previous reports that the microsomal and mitochondrial GPAT isoforms are distinct (1,2,11) and that their amino acid sequences are very different. A two-dimensional Western blot analysis was performed in order to distinguish the anti-GPAT immunoreactive proteins in wild type and mtGPAT Ϫ/Ϫ liver mitochondria.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The mitochondria were not contaminated with endoplasmic reticulum (Table I), and no immunoreactive protein was detected in the microsome fraction (Fig. 3A), consistent with previous reports that the microsomal and mitochondrial GPAT isoforms are distinct (1,2,11) and that their amino acid sequences are very different. A two-dimensional Western blot analysis was performed in order to distinguish the anti-GPAT immunoreactive proteins in wild type and mtGPAT Ϫ/Ϫ liver mitochondria.…”
Section: Resultssupporting
confidence: 90%
“…Because only the mitochondrial GPAT isoform has been cloned (11,12), changes in activity of the two isoenzymes can be compared, but not changes in mRNA abundance or protein expression. In general, mtGPAT mRNA, protein, and activity in liver and adipose tissue increase with carbohydrate feeding and with insulin stimulation, whereas microsomal GPAT activity does not change (11,(13)(14)(15). In addition, mtGPAT mRNA is upregulated by sterol regulatory element-binding protein-1c, a potent activator of lipogenesis (16).…”
mentioning
confidence: 99%
“…Our laboratory originally cloned mtGPAT, which was the first mammalian enzyme in TAG and phospholipid biosynthesis to be cloned [15][16][17]. While mammalian cells are known to have two GPATs, one in the ER (microsomal GPAT) and another in the mitochondria (mtGPAT), microsomal GPAT has not been cloned [13,18].…”
Section: Biosynthesis Of Triacylglycerolmentioning
confidence: 99%
“…Most enzymes in TAG synthesis are intrinsic membrane proteins and their substrates and products are hydrophobic, making purification and kinetic analysis difficult. Cloning and characterization of the enzymes mentioned previously has only been achieved during the last decade following advances in molecular biological techniques.Our laboratory originally cloned mtGPAT, which was the first mammalian enzyme in TAG and phospholipid biosynthesis to be cloned [15][16][17]. While mammalian cells are known to have two GPATs, one in the ER (microsomal GPAT) and another in the mitochondria (mtGPAT), microsomal GPAT has not been cloned [13,18].…”
mentioning
confidence: 99%
“…The gene encoding the mammalian mitochondrial NEM-resistant GPAT1 (mtGPAT1, GPAM) was identified a decade ago and was shown to play a key role in liver TAG synthesis (6)(7)(8). Although initial reports suggested that mtGPAT1-deficient mice have decreased adipose tissue mass (6), more recent studies found little effect of mtGPAT1 deficiency on the development of obesity (7).…”
mentioning
confidence: 99%